PENERAPAN METODE ACTIVITY-BASED COSTING SYSTEM DALAM MENENTUKAN BESARNYA TARIF JASA RAWAT INAP: Studi Kasus pada RSUD Mayjen H. A. Thalib Kerinci - Rio Baviga (Gapenas Publisher, 2021)
This study aims to determine : 1) How the application of the method of Activity-Based Costing System in determining the amount of inpatient hospital service for RSUD Mayjen H. A. Thalib Kerinci?, 2) How big is the comparison of inpatient service rates using traditional methods and the activity based costing system method? This research was conducted at RSUD Mayjen H. A. Thalib Kerinci. The analytical method used in this research is a quantitative descriptive analysis method that shows and compares the method of determining inpatient service rates applied by RSUD during 2019 using an activity-based costing system. Based on the results of the study showed that : from the calculation of hospitalization rates using the ABC method, when compared with traditional methods, the ABC method gave greater results except for the Suite Room, VVIP and VIP classes which gave smaller results. This is because the imposition of overhead costs on each product is only charged to one cost driver. As a result there tends to be a distortion in the imposition of overhead costs. Whereas in the abc method, the overhead costs on each product are charged to many cost drivers. So in the abc method, it has been able to allocate activity costs to each room appropriately based on the consumption of each activity